Social Media Exposure and English Writing Proficiency of Grade 11 Students in a Philippine Public High School - Esman, Esterline Nograles; Madrigal, Dennis V.; Mascuňana, Chona G. (Technium Social Sciences Journal, 2021)
Social media has become a vital part of people's daily communication activities in all walks of life and had globalized its use, especially to learners. Learners' propensity to social media has come to increasing involvement in the internet cafes. Since its medium of instruction is mainly English, it influences learners' English communication skills, especially in writing. The paper examined the relationship between the extent of exposure to social media and the English writing proficiency of Grade 11 students in a Philippine public senior high school. Using the descriptive research design, data were collected using the self-administered survey questionnaire and analyzed using descriptive and inferential statistics. The results reveal that the respondents demonstrated an average extent of exposure to social media when grouped according to their demographic profiles and an internet connection and were average in their English writing proficiency level. The results also established a slight positive significant relationship between exposure to social media and English writing proficiency. Generally, the paper validates how social media exposure influences English writing proficiency as intervened by the academic language education.